1999
DOI: 10.1093/bja/83.5.747
|View full text |Cite
|
Sign up to set email alerts
|

Continuous auditory monitoring—how much information do we register?

Abstract: We have studied response times of 30 anaesthetists to a standardized episode of arterial oxygen desaturation in a simulated patient, randomized to the use of either a fixed or variable pitch pulse oximeter. We wished to determine if a variable auditory signal was important in detecting adverse events. A variable pitch pulse signal had a shorter time to recognition of desaturation (P < 0.0001), with a mean response time of 32 s, compared with 129 s for the fixed pitch signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…In a previous simulation study of decreasing oxygen saturation, a mean response time of 32 s was found [17], compared with 12 s in ours. The response time to atrial fibrillation was previously studied between different groups, with a mean response time of 176, 39 and 31 s, respectively [21], compared with 10 s in our study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In a previous simulation study of decreasing oxygen saturation, a mean response time of 32 s was found [17], compared with 12 s in ours. The response time to atrial fibrillation was previously studied between different groups, with a mean response time of 176, 39 and 31 s, respectively [21], compared with 10 s in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Therefore, all participants were used to the simulation environment. Furthermore, participants in simulation sessions often expect an event to occur and therefore they tend to be very vigilant during simulation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Using the variable pitch auditory signal of a pulse oximeter, a clinician can detect changes in a patient's heart rate and oxygen saturation level (SpO 2 ) while performing other visually demanding tasks, or when the visual display of the pulse oximeter is out of the line of sight . However, clinicians cannot accurately estimate the absolute level of SpO 2 without reference to the pulse oximeter's visual display .…”
Section: Introductionmentioning
confidence: 99%
“…Sonification also allow several metrics to be displayed simultaneously using variations in pitch, timbre, volume and period (Pollack and Ficks, 1954;Flowers, 2005). For these reasons, sonification is widely used in medicine for monitoring crucial metrics of patient health (Craven and Mcindoe, 1999; Morris and Mohacsi, 2005;Sanderson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%